2011
DOI: 10.1001/jama.2011.1433
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplements in Pregnancy and Severe Language Delay in Children

Abstract: Context Prenatal folic acid supplements reduce the risk of neural tube defects and may have beneficial effects on other aspects of neurodevelopment. Objective To examine associations between mothers' use of prenatal folic acid supplements and risk of severe language delay in their children at age 3 years. Design, Setting, and Patients The prospective observational Norwegian Mother and Child Cohort Study recruited pregnant women between 1999 and December 2008. Data on children born before 2008 whose mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
175
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(188 citation statements)
references
References 38 publications
10
175
0
3
Order By: Relevance
“…16,27 recent studies indicate that maternal folic acid supplementation in early pregnancy may prevent neurodevelopmental disorders in children. [28][29][30][31] a study from california found decreased risk of autistic disorder in children whose mothers had used prenatal vitamin supplements containing folic acid. 28 Studies based on a norwegian child cohort showed that maternal use of folic acid in early pregnancy was associated with decreased risk of both severe language delay and autistic disorder in the offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,27 recent studies indicate that maternal folic acid supplementation in early pregnancy may prevent neurodevelopmental disorders in children. [28][29][30][31] a study from california found decreased risk of autistic disorder in children whose mothers had used prenatal vitamin supplements containing folic acid. 28 Studies based on a norwegian child cohort showed that maternal use of folic acid in early pregnancy was associated with decreased risk of both severe language delay and autistic disorder in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…28 Studies based on a norwegian child cohort showed that maternal use of folic acid in early pregnancy was associated with decreased risk of both severe language delay and autistic disorder in the offspring. 29,30 information about maternal use of folic acid supplements before and during pregnancy is available in the norwegian birth registry, but only for children born in 1999 or later. even then, folate use is substantially underreported.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, higher intakes or blood concentrations of vitamin B-12 (5,6), choline (7,8), betaine (7), and Met (9)(10)(11) during the periconceptional period have been inversely associated with the risk of NTDs, albeit less consistently, compared with folic acid. Additionally, high periconceptional folate exposure has been associated with improved neurodevelopment (12)(13)(14)(15) and a reduction in the risk of various pediatric cancers (16)(17)(18) in offspring. In contrast, high periconceptional folic acid exposure has been shown in some studies, but not all, to increase the risk of asthma (19), atopic dermatitis (20), obesity, and metabolic syndrome (21) and in one study to increase the risk of a detrimental effect on psychomotor development (22).…”
Section: Introductionmentioning
confidence: 99%
“…Four reports from two studies suggest that periconceptional vitamin use, dietary folic acid intake, or folic acid supplementation are associated with a decreased risk of ASD diagnosis, severe language delay, and emotional problems. (Roth, Magnus et al 2011; Schmidt, Hansen et al 2011; Schmidt, Tancredi et al 2012; Steenweg-de Graaff, Roza et al 2012; Suren, Roth et al 2013) In one study, the association between prenatal vitamin intake and ASD diagnosis was modified by maternal polymorphisms in folate transport and bioavailability genes. (Schmidt, Hansen et al 2011) While these findings suggest a role for folate status in the development of ASD, the association between biomarkers of prenatal folate status and child ASD or autistic-behaviors has not been directly assessed.…”
mentioning
confidence: 99%